From Selye's and Szabo's Cysteamine-Duodenal Ulcer in Rats to Dopamine in the Stomach: Therapy Significance and Possibilities - Predrag Sikiric; Alenka Boban Blagaic; Ivan Krezic; Helena Zizek; Luka Kalogjera; Ivan Maria Smoday; Vlasta Vukovic; Katarina Oroz; Helen Marie Chiddenton; Sara Buric; Marko Antunovic; Slaven Gojkovic; et al. (MDPI AG, 2023)
We reviewed gastric ulcer healing by dopamine considering several distinctive duodenal key points. Selye and Szabo describe the cysteamine-induced duodenal ulcer in rats as a duodenal stress ulcer in patients. Szabo's cysteamine duodenal ulcer as the dopamine duodenal healing and cysteamine as a dopamine antagonist signifies the dopamine agonists anti-ulcer effect and dopamine antagonists ulcerogenic effect. From these viewpoints, we focused on dopamine and gastric ulcer healing. We mentioned antecedent studies on the dopamine presence in the stomach and gastric juice. Then we reviewed, in the timeline, therapy significance arising from the anti-ulcer potency of the various dopamine agonists, which is highly prevailing over the quite persistent beneficial evidence arising from the various dopamine antagonists. Meanwhile, the beneficial effects of several peptides (i.e., amylin, cholecystokinin, leptin, and stable gastric pentadecapeptide BPC 157, suggested as an acting mediator of the dopamine brain-gut axis) were included in the dopamine gastric ulcer story. We attempt to resolve dopamine agonists/antagonists issue with the dopamine significance in the stress (cysteamine as a prototype of the duodenal stress ulcer), and cytoprotection (cysteamine in small dose as a prototype of the cytoprotective agents; cysteamine duodenal ulcer in gastrectomized rats). Thereby, along with dopamine agonists' beneficial effects, in special circumstances, dopamine antagonists having their own ulcerogenic effect may act as "mild stress (or)" or "small irritant" counteracting subsequent strong alcohol or stress procedure-induced severe lesions in this particular tissue. Finally, in the conclusion, as a new improvement in further therapy, we emphasized the advantages of the dopamine agents' application in lower gastrointestinal tract therapy.